Relevance of indicators of clinical supervision strategies in nursing - Duarte José Esteves Pinto; Margarida Reis Santos; Regina Maria Pires (Universidade Federal do Ceará, 2017)
To identifying the indicators of strategies of clinical supervision in nursing that nurses consider more relevant. Methods: it is a descriptive and exploratory research with a quantitative approach. A questionnaire was constructed to collect data, applied to a sample of 316 nurses who performed functions in a hospital context and primary health care. Results: the relevance attributed by the nurses to the indicators of clinical supervision strategies, especially the reflexive processes, as well as to methods directed to action and demonstration, are highlighted. Conclusion: the indicators identified in the study constitute an important step in the structuring and evaluation of supervision processes, contributing to the improvement of quality and safety of care.